Self-assembled monolayers formed using zero net curvature norbornylogous bridges: The influence of potential on molecular orientation - Eggers, P.; Da Silva, P.; Darwish, Nadim; Zhang, Y.; Tong, Y.; Ye, S.; Paddon-Row, M.; Gooding, J. (American Chemical Society, 2010)
A new class of electroactive norbornylogous bridges, with no net curvature, that form self-assembled monolayers on gold electrodes were studied by electrochemistry and in situ infrared spectroscopy. The influence of the electrode potential on the structure and conformation of the self-assembled monolayers (SAMs) was investigated. This was performed using two different lengths of rigid norbornylogous bridges with terminal ferrocene moieties and ?-hydroxyalkanethiols. It was found that single component monolayers of the rigid norbornylogous bridges changed their tilt angle with their transition from the ferrocene to ferricinium. However, when the norbornylogous SAMs were diluted with?-hydroxyalkanethiols the tilt angle remained unchanged upon oxidation of ferrocene to ferricinium. It was also observed that the tilt angle of the diluent, ?-hydroxyalkanethiols changed at potentials exceeding 500 mV. © 2010 American Chemical Society.